Hoch- und spätmittelalterliche Siedlungsräume im südlichen Bayerischen Wald.: Ein Beitrag zur Stellung der Hofacker-/Gelängeflur - Haversath, Johann-Bernhard (ERDKUNDE, 1991)
The colonization of the southern Bavarian Forest during the late Middle Ages took a greater and more different course than the known results of historical and territorial investigations suggested. The settlement-activities at the beginning of the late Middle Ages had two effects: on the one hand the settled area was extended into the forest (frontier-line), on the other hand the earlier settled districts became more and more compact (interior colonization). The planned settlements (linear and place-villages with so called Hofacker-/Gelängeflur) arose only at places, where new land was systematically colonized after clearances. Here the so-called Hofacker-/Gelängeflur proved to be a system of allotments which was very weil adapted to the necessities of hilly ground and agriculture. The model of type-succession does not seem to be suitable for showing the development of colonization in the southern Bavarian Forest. The complex reality will find a better explanation if we suggest a process of innovation. Such a model embraces the regular settlements with garden allotments at second-best places, as weil as the regular settlements with so-called Hofacker-/Gelängeflur in the so far unsettled districts.